A novel c.2326G>A KIT pathogenic variant in piebaldism - Shi, Weili (Am J Transl Res, 2020)
Introduction: Piebaldism is a rare autosomal dominant disorder characterized by congenital patchy depigmentation of the scalp, forehead, trunk, and limbs. The KIT gene is the mainly causative gene to this disease. But how KIT is involved in piebaldism remains unclear. Methods: Whole exome sequencing was used to explore the genetic cause of a familial case of piebaldism. Sanger sequencing was used to validate the variant. To further examine the variant’s pathogenicity, the wild type and the mutated KIT plasmids were constructed and transfected into HEK293T cells. Next STAT5 expression, a signaling target of KIT, was detected by western blotting to explore the potential molecular mechanism of the variant in piebaldism. Based on the classification of the given variant, prenatal diagnosis was further performed in this family. Results: A novel pathogenic variant of KIT c.2326G>A (NM_000222.2) was identified in this family. The phosphorylation of STAT5 was reduced in the mutant KIT transfected cells compared to the wild type after stem cell factor (SCF) treatment, indicating that the KIT signaling was dysfunctional and supported that the variant was a pathogenic one. Prenatal diagnosis results indicated that the fetus exhibited the same genotype as the proband. Conclusion: We identified a novel KIT pathogenic variant in the patient with piebaldism to expand the variation spectrum of KIT. The functional study indicated that the mutant KIT was dysfunctional in KIT signaling. The pathogenic variant identification enriches the knowledge about the genotype/phenotype correlation and could serve as the basis for genetic counseling and prenatal diagnosis.